1999
DOI: 10.1002/1529-0131(199907)42:7<1378::aid-anr11>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis and risk of falls, rates of bone loss, and osteoporotic fractures

Abstract: Despite having increased BMD compared with controls, subjects with OA did not have a significantly reduced risk of osteoporotic fracture, although there was a trend toward a reduced risk of femoral neck fractures in subjects with severe radiographic OA. The failure of the observed increase in BMD to translate into a reduced fracture risk may be due, in part, to the number and type of falls sustained by subjects with OA. Patients with OA should not be considered to be at a lower risk of fracture than the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
1
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(135 citation statements)
references
References 35 publications
4
121
1
9
Order By: Relevance
“…Other studies have analyzed the relationship between peripheral OA and fragility fractures and have demonstrated either an increased risk of fracture (18), no change (14,16), or a decreased risk (11,13). OA was reported either at the hip, knees, or hands, or sometimes with a global evaluation without specifying the site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have analyzed the relationship between peripheral OA and fragility fractures and have demonstrated either an increased risk of fracture (18), no change (14,16), or a decreased risk (11,13). OA was reported either at the hip, knees, or hands, or sometimes with a global evaluation without specifying the site.…”
Section: Discussionmentioning
confidence: 99%
“…A protective effect of OA on hip fracture risk was suggested by case-control studies of patients with self-reported OA (12,13). Prospective studies failed to show any decrease in fracture incidence in OA patients (14)(15)(16). Other studies have shown an increased fracture risk associated with OA evaluated by radiography (17,18).…”
mentioning
confidence: 99%
“…A positive association between BMD and OA would imply that individuals with OA should have a reduced risk of fracture; however, several studies have instead observed either no difference in fracture incidence between OA affected individuals and controls 39,49 or an increase in fracture risk, 50 although it should be noted that the type of OA definition used in these studies has varied. It has long been speculated that this may relate to an increased risk of falls in OA cases, 50 and indeed a recent large prospective study supported this hypothesis, showing that an association between (selfreported) OA and fracture was largely attenuated by adjusting for incident falls.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 96%
“…Studies examining the relationship between OA and rates of bone loss, also inversely related to BMD, have reached similarly opposing conclusions, with bone loss in individuals with OA found to be reduced, 16 increased, 8,38 or variable depending upon the site of assessment of both OA and BMD. 39 In a longitudinal study, more rapid bone loss over an 8-year period was associated with an increased risk of progressive OA at the knee. 17 Findings from prospective studies that greater bone loss and turnover may be associated with more rapid OA progression would seem at odds with those discussed earlier, suggesting that higher, rather than lower, BMD is a risk factor for OA.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 99%
“…[5][6][7] The reason for this is not known, but may be related to an increased incidence of falling in older adults with lower extremity OA, which exposes them to greater risk of fracture. In a review of 16 fall-risk studies, 8 one of the priority risks identified was the presence of any type of arthritis, which had a higher mean relative risk (RR) of predicting future falls than either age or cognitive status.…”
Section: Ré Sumémentioning
confidence: 99%